The resurrection of Gutierrezia ameghinoi (Asteraceae, Astereae, Solidagininae), a species from Patagonia, Argentina - Ratto, Francisco; Bartoli, Adriana (Phytotaxa, 2015)
Gutierrezia ameghinoi Speg., a species from the Argentinean Patagonia, is resurrected. Its geographical distribution and habitat are described. A key to distinguish G. ameghinoi from co-occurring relatives is included. The species is illustrated for the first time.